2017
DOI: 10.1111/ppl.12557
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tobacco plants having a higher level of methionine are more sensitive to oxidative stress

Abstract: Methionine is an essential amino acid the low level of which limits the nutritional quality of plants. We formerly produced transgenic tobacco (Nicotiana tabacum) plants overexpressing CYSTATHIONE γ-SYNTHASE (CGS) (FA plants), methionine's main regulatory enzyme. These plants accumulate significantly higher levels of methionine compared with wild-type (WT) plants. The aim of this study was to gain more knowledge about the effect of higher methionine content on the metabolic profile of vegetative tissue and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…The transcript expression of AtAPR2 and AtGR1 genes increased under oxidative stress at a relatively similar rate (Figure S9). This result is in accordance with previous studies, which showed that under abiotic stresses, the expression of key genes in the sulfur assimilation pathway increased together with an increase in the synthesis of cysteine and glutathione (Bick et al , ; Queval et al , , ; Hacham et al , ). Therefore, these results suggest a link between the higher levels of these genes to the synthesis of cysteine and glutathione under stress, as we propose here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The transcript expression of AtAPR2 and AtGR1 genes increased under oxidative stress at a relatively similar rate (Figure S9). This result is in accordance with previous studies, which showed that under abiotic stresses, the expression of key genes in the sulfur assimilation pathway increased together with an increase in the synthesis of cysteine and glutathione (Bick et al , ; Queval et al , , ; Hacham et al , ). Therefore, these results suggest a link between the higher levels of these genes to the synthesis of cysteine and glutathione under stress, as we propose here.…”
Section: Discussionsupporting
confidence: 93%
“…This sensitivity might be the consequence of a lesser conversion of GSSG to GSH, but the results of the current study suggest an additional explanation: the sensitivity could result from the lower production of cysteine and glutathione in these plants during the stress due to lower GR activity that affects APR activity. It was previously proposed that the delta changes in metabolite contents such as glutathione between non‐stress and stress conditions is a crucial factor for enabling the plants to cope with stress conditions, as is shown when oxidative stress was used (Hacham et al , ), suggesting that this ability was reduced in the GR‐RNAi lines.…”
Section: Discussionmentioning
confidence: 97%
“…Threitol, a four‐carbon sugar alcohol, has been detected in plant species such as Nicotiana tabacum and Coffea arabica , as well as in mycelia of Armillaria fungal species (Birkinshaw, Stickings, & Tessier, ; Hacham, Matityahu, & Amir, ; Martins, Araújo, Tohge, Fernie, & DaMatta, ). Hence, it was unclear whether the threitol detected in the E. grandis roots with the current study was derived from the fungal pathogen or the E. grandis itself.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon also might occur in rosette leaves. Indeed, a metabolic profiling analysis of tobacco leaves overexpressing AtCGS shows that they have higher contents of stress-related metabolites, and they were more sensitive to short-and long-term oxidative stresses (Hacham et al, 2017). Since the SMM cycle is considered futile, it would be interesting to investigate whether AtHMTs and AtMMT are found in the same type of cells within seeds and leaves and whether SMM can be stored in other organelles, such as vacuoles, in order to discard its futility when HMTs and MMT cooperate at the same cell.…”
Section: This Study Implies Other Possible Roles Of the Smm Cycle In mentioning
confidence: 99%